Pengaruh Influencer Marketing, Fear Of Missing Out (FOMO), dan Online Customer Review Terhadap Keputusan Pembelian pada Produk Glad2glow di Tiktok Shop - Yesa Salisatin Fitriningtyas; Misti Hariasih; Sumartik Sumartik (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The development of social media as a digital marketing tool has changed the way consumers make purchasing decisions, especially on the TikTok Shop platform. This study was conducted to determine the influence of influencer marketing, Fear of Missing Out (FOMO), and online customer reviews on purchasing decisions for Glad2glow products on TikTok Shop. A quantitative approach was used with a survey method. The sample consisted of 100 respondents who had previously purchased Glad2glow products through TikTok Shop. The sampling technique used was purposive sampling based on specific criteria. Data were collected through questionnaires and analyzed using SPSS version 26 through validity and reliability tests, t-tests, and multiple linear regression analysis. This study proves that influencer marketing, Fear of Missing Out (FOMO), and Online Customer Reviews positively and significantly influence purchasing decisions. This research indicates that influencer marketing-based strategies, psychological drives caused by trends and urgency, and online customer reviews play an important role in driving consumer purchasing decisions on social media-based e-commerce platforms.